Gabapentin, Pregabalin, and Placebo in Reducing Opioid Withdrawal Symptoms in Opioid-dependent Individuals: A Randomized-controlled Trial. (June 2018) - Kheirabadi, Gholam R.; Salehi, Mehrdad; Bahrami, Mahboobe; Maracy, Mohammad R.
Abstract : Objective: The objective of this study was to compare the efficacy of pregabalin and gabapentin in patients undergoing outpatient treatment for opiate withdrawal. Materials and Methods: In a 4-week double-blinded, randomized, placebo-controlled trial of pregabalin and gabapentin in buprenorphine-assisted detoxification (BAD) in the Specialized Addictive Behaviors Unit, an outpatient unit for the treatment of patients with an addictive disorder serving the city of Isfahan (Iran), 50 outpatients, 45 male individuals and 5 female individuals, aged 20 to 60 years, who met DSM-V criteria for opiate dependence, were randomly assigned to receive adjunctive treatment with either pregabalin (450 mg/d), gabapentin (1600 mg/d), or placebo under double-blinded conditions. The severity of subjective withdrawal symptoms were measured using the Short Opioid Withdrawal Scale (SOWS) at 5 stages. Results: Despite the effect of pregabalin and gabapentin on controlling some of the withdrawal symptoms, no significant differences were reported among the 3 groups. Conclusions: Dosages of 450 mg/d of pregabalin and 1600 mg/d of gabapentin are not significantly superior to placebo in controlling opiate withdrawal symptoms.